2018
DOI: 10.1155/2018/4863757
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of SNP rs2645429 in Farnesyl-Diphosphate Farnesyltransferase 1 Gene Promoter with Susceptibility to Lung Cancer

Abstract: Background and Purpose The mevalonate pathway is one of the major metabolic pathways that use acetyl-CoA to produce sterols and isoprenoids. These compounds can be effective in the growth and development of tumors. One of the enzymes involved in the mevalonate pathway is FDFT1. Different variants of this gene are involved in the risk of suffering various diseases. The present study examined the relationship between FDFT1 rs2645429 polymorphism and the risk of nonsmall cell lung cancer (NSCLC) in a population f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…However, FDFT1 has seldom been studied in the field of cancer research. Limited studies addressed FDFT1 in prostate cancer 35 , ovarian cancer 46 , and lung cancer 47 , but there is no information on the function of FDFT1 in CRC. Therefore, we selected FDFT1 as the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…However, FDFT1 has seldom been studied in the field of cancer research. Limited studies addressed FDFT1 in prostate cancer 35 , ovarian cancer 46 , and lung cancer 47 , but there is no information on the function of FDFT1 in CRC. Therefore, we selected FDFT1 as the target gene.…”
Section: Discussionmentioning
confidence: 99%
“…The single-nucleotide polymorphism of HMGCR, rs12916, is associated with the subgroups of attained age for lung cancer (111) and the C allele of the SQS rs2645429 polymorphism gene can be a risk factor for non-small cell lung cancer (NSCLC) (116). Three key enzymes of the mevalonate pathway, FPPS, SQS and GGPPS, are also associated with stage and metastasis of NSCLC (117)(118)(119).…”
Section: Lung Cancermentioning
confidence: 99%
“…For example, according to the single nucleotide polymorphism database (dbSNP) (http://www.ncbi.nlm.nih.gov/ projects/SNP; build 128), SNPs are found in 244 pieces within 2 kb of the 5 side and 500 bp of the 3 side of the gene region of FDFT1, but quite a few parts have not been verified yet [45]. The significance of the genetic diversity of the FDFT1 gene in diseases such as cancer and hepatitis C has been partially studied [111]. For example, investigating the SNP rs2645424 polymorphism of this gene in hepatitis C patients, it was found that this polymorphism was associated with progressive fibrosis in patients, not fatty liver [112].…”
Section: The Role Of Fdft1 In Cancermentioning
confidence: 99%